FRICTORQ: evaluation of friction coefficient in the presence of cosmetic creams - Macedo, Dinis Pereira de (2012)
There are numerous applications in which products or materials are in contact with the human body, including the skin, such as clothing, fine papers and even cosmetics. In this sense, and with special emphasis on cosmetic products, there are several parameters for assessing its quality and applicability. The coefficient of friction is one of these parameters for the objective assessment of a concept commonly known by touch. This paper aims to review the main developments that led to the redesign of FRICTORQ device for measuring the coefficient of friction of cosmetic creams, and the first preliminary tests carried out with cosmetic products are also presented, analysed and discussed. It was determined that the friction coefficient of a moisturizing cream is higher than the one obtained for an exfoliating cream.